PENGARUH PENGELOLAAN UANG SAKU, MODERNITAS, KECERDASAN EMOSIONAL, DAN PEMAHAMAN DASAR EKONOMI TERHADAP RASIONALITAS PERILAKU KONSUMSI SISWA KELAS X IIS MAN 1 MALANG - Rizky Fiqriyah; Hari Wahyono; Ro'ufah Inayati (Jurnal Pendidikan Ekonomi, 2016)
In the daily life, humans cannot be separated with economics activity to fulfil varying of their needs which are not balanced with the available resources, so they have to behave rationally in economic activity, especially consumption. This study aims to determine the partial and simultaneous effect of allowance management, modernity, emotional quotient, and economic literacy against rationality of consumption behaviour’s students in the 10th grade of Social Science MAN 1 Malang.This research used quantitative approach with explanation research. The population are students in the 10th grade of Social Science MAN 1 Malang with a sample of 54 students is calculated using Slovin Formula and sampling technique is proportional random sampling. The data were obtained through questionnaires and written test. To analyze the data, this research used multiple linear regression analyze technique. The result in this research showed: (1) allowance management affects the rationality of consumption behaviour for students in the 10th grade of Social Science MAN 1 Malang, (2) modernity affects the rationality of consumption behaviour for students in the 10th grade of Social Science MAN 1 Malang, (3) emotional quotient affects the rationality of consumption behaviour for students in the 10th grade of Social Science MAN 1 Malang, (4) economic literacy affects the rationality of consumption behaviour for students in the 10th grade of Social Science MAN 1 Malang, (5) allowance management, modernity, emotional quotient, and economic literacy affect simultaneously to the rationality of consumption behaviour for students in the 10th grade of Social Science MAN 1 Malang.